1999
DOI: 10.1046/j.1365-2508.1999.00261.x
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial carcinoma in postmenopausal patients using hormone replacement therapy: a report on four cases

Abstract: Objective To report the occurrence of endometrial carcinoma in polyps in postmenopausal patients using hormone replacement therapy (HRT). Setting A private hospital with facilities for carrying out hysteroscopy. Subjects Four postmenopausal patients who developed endometrial carcinoma while using HRT. Interventions Hysteroscopy with biopsy, immunohistochemical investigation for oestradiol, progesterone receptors and p53 overexpression. Results All four cases of carcinoma were associated with endometrial polyps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…The high incidence of endometrial polyps in tibolone users which was seen in the present study confirms previous observations carried out with hysteroscopy; these revealed that the presence of uterine intracavitary lesions accounts for a large number of the bleeding episodes reported during tibolone treatment 5,6 . The higher incidence of endometrial polyps in menopausal patients using HRT has also been observed in previous studies 8,10 …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The high incidence of endometrial polyps in tibolone users which was seen in the present study confirms previous observations carried out with hysteroscopy; these revealed that the presence of uterine intracavitary lesions accounts for a large number of the bleeding episodes reported during tibolone treatment 5,6 . The higher incidence of endometrial polyps in menopausal patients using HRT has also been observed in previous studies 8,10 …”
Section: Discussionsupporting
confidence: 92%
“…Ginsburg & Prelevic 5 have also reported the occurrence of endometrial carcinomas in tibolone users with bleeding, and in one patient the carcinoma occurred in association with a cervical polyp. The presence of endometrial carcinomas associated with uterine polyps has also been observed in postmenopausal patients who had been using other forms of HRT 10 …”
Section: Discussionmentioning
confidence: 95%